Pengaruh Kompres Hangat Serai Merah ( Cymbopogon Nardus) terhadap Penurunan Skala Nyeri Punggung Bawah pada Nelayan di Desa Latuhalat Kecamatan Nusaniwe - Dessy Latulette; Sahrir Silehu; Yerry Soumokil (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Introduction: Low back pain is one of the most common musculoskeletal disorders in the world. In general, this pain is caused by muscle stretching and increasing age which will cause the intensity of exercise and movement to decrease. This will cause the back and abdominal muscles to become weak. Objective: In this study, to analyze the effect of warm compresses of red lemongrass (cymbopogon nardus) on reducing the scale of lower back pain in fishermen in Negeri Latuhalat, Nusaniwe District. Method: Using a one group pre test-post test design, this research design is included in the Pre-Experimental research type and the sample size is 56 fishermen using instruments in the form of SOPs and observation sheets. The analysis used is the Willcoxon test. Results: It was found that there was an effect of warm red lemongrass (Cymbopogon nardus) compresses on reducing the scale of lower back pain in fishermen (p-value = 0.000). Conclusion: There is an influence between the pain scale before and after being given a warm compress of red lemongrass (cymbopogon nardus) on reducing the scale of lower back pain in fishermen in Negeri Latuhalat, Nusaniwe District.